Proximal cut-out in pertrochanteric femural fracture - Valentini, Roberto; Martino, Marcellino; Piovan, Gianluca; De Fabrizio, Giovanni; Fancellu, Giovanni (Acta Biomedica Atenei Parmensis, 2014)
The average age of population is increasing in parallel with the worldwide incidence of fractures of the proximal femur; among all of them, 45% is represented by pertrochanteric fractures. Many other significant co-morbidity and even mortality are associated to this fractures (osteoporosis, malnutrition, decreased physical activity, reduced visual acuity, neurological deficits, asthenia, balance disorders and altered reflexes). Due to osteoporosis, the greater frequency of these fractures occurs to elderly women. Among a total of 630 patients with pertrochanteric fracture treated in the Orthopedic Clinic of Trieste from January 2003 to December 2011, 16 cases were about Cut-out (5 males and 11 females). The mean follow-up after the revision surgery was 18 months. The aim of the study was to understand if in pertrochanteric fractures the best osteosynthesis can be guaranteed by the placement of an intramedullary nail or by positioning of plate and screws. It was established that, using intramedullary nail, the best target is to have a good positioning of the method of synthesis with a “Tip-Apex Distance” (TAD) of less than 25 millimeters.